The impact of digital transformation on corporate ESG performance: empirical evidence from Chinese listed companies / Sixin Ren and Salmi Mohd Isa - Ren, Sixin; Mohd Isa, Salmi (Faculty of Business and Management, 2023)
This study uses information from listed firms on China's Shanghai and Shenzhen A-share markets to analyze how the digital transformation has impacted corporate Environmental, Social, and Governance (ESG) performance between 2010 and 2020. The empirical results demonstrate that the influence of digital transformation on ESG performance is only marginally favorable. Important processes including green technology development, information transparency, decision-making, and operational efficiency all contribute to a company's ESG performance through digital transformation. According to the study's findings, non-state-owned enterprises, younger corporations, and larger companies are more likely to have positive benefits of digital transformation on ESG performance. These findings have practical implications for organizations and decision-makers seeking to enhance ESG performance through digital transformation.